Investigating the Various Effects of Pear Packaging Box Design Factors Subject to Stress Forces. Issue 1 (2nd January 2020) - Azadbakht, Mohsen; Rayeni Moghbeli, Hamid; Vahedi Torshizi, Mohammad
ABSTRACT: The present research deals with various design factors materials)Polyethylene, Polypropylene and Lorg Wood(, hole type, holes' spacing and box edge thickness) in regard to stresses exerted onto the pear packaging boxes. At first, Solid Works 2018 Software was employed to design 81 boxes and the material factors (polyethylene, polypropylene and Lorg wood), box edge thickness (0.35, 0.5 and 0.65 cm), holes' type (circular, square and rectangular) and holes' spacing (2.1, 2.4 and 2.7 cm) were taken into account. The entire boxes were analyzed using Ansys 2018 and the maximum stress rates were calculated. Then, the obtained stress rates were subjected to statistical analysis through taking advantage of SAS 9.2 software. The study results indicated that equivalent stress, total deformation, equivalent elastic strain, shear elastic strain, normal stress and shear stress correspondingly are equal to 638.8pa (rectangular hole type and 0.5 cm edge thickness), 1.91 × 10 −11  m (circular hole type and 0.5 cm edge thickness), 3.7 × 10 −9  m/m (2.7 cm hole spacing and circular hole type), 4.43 × 10 − 9 m/m (0.50 cm box edge thickness and circular hole type), 305.66pa (2.7 cm hole spacing and circular hole type) and 225pa (rectangular hole type and 0.5 cm box edge thickness); the highest amounts were 5914.7pa (square hole type and 0.65 cm edge thickness), 1.11 × 10 −9  m (square hole type and 0.5 cm box edge thickness), 3.21 × 10 −8  m/m (0.65 cm box edge thickness and square hole type), 4.17 × 10 −8  m/m (0.65 cm box edge thickness and square hole type), 2880.6pa (0.65 cm box edge thickness and square hole type), 2304.8pa square hole type and 0.65 cm box edge thickness, respectively.